Safety analysis and reliability assessment of engineering structures – The success story of SARA. Issue 2 (22nd April 2019) - Strauss, Alfred; Novák, Drahomír; Lehký, David; Vořechovský, Miroslav; Teplý, Břetislav; Pukl, Radomír; Červenka, Vladimír; Eichinger‐Vill, Eva M.; Santa, Ulrich
Abstract: The concept for the safety assessment of concrete structures integrating nonlinear finite element analysis with stochastic and reliability technology into an advanced engineering tool is presented. The basic aim of the stochastic nonlinear analysis is to calculate the safety index (and failure probability) of an existing engineering structure, which characterizes its reliability. The nonlinear solution enables a realistic estimation of the structural response statistics to be obtained (failure load, deflections, cracks, stresses, etc.). The development of possibility of randomization for such computationally intensive problems was part of the project Safety Analysis and Reliability Assessment of Engineering Structures (SARA). Latin hypercube sampling has been used in SARA in order to keep the number of required simulations at an acceptable level. Statistical correlation, which is important for a realistic solution, was also imposed in SARA by using a stochastic optimization technique called simulated annealing. The sensitivity of results to random input parameters can be evaluated using nonparametric rank‐order correlation coefficients. The presented project SARA focusing on the safety assessment of engineering structures supersedes the usual methods based on simplified formulas. SARA supports a higher level of decision‐making process in bridge administration and maintenance of transport macrostructure. The object of this article is to present the diverse developments of the project SARA and to honor Professor Konrad Bergmeister, who was the frontrunner and chair of SARA and was mainly responsible for the SARA project initiation and its fruitful and amazing developments.